Long-term impacts of the oportunidades conditional cash transfer program on rural youth in Mexico - Jere R. Behrman; Susan W. Parker; Petra E. Todd (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper studies the long-term effects of participation in the Mexican Oportunidades program on a variety of outcomes and behaviors of rural youth in Mexico. It analyzes data from a social experiment, which randomly phased-in the program in rural Mexican villages. In 1997, 320 villages (the treatment group) were randomly selected for early incorporation into the program and 186 villages (the control group) were designated as a control group to be incorporated eighteen months later. This paper examines whether differential exposure to the program significantly impacted educational attainment, labor market outcomes, marriage, migration and cognitive achievement of youth. The results show positive impacts of longer exposure on grades of schooling attained, but no effects on achievement tests. With respect to work, we find an overall reduction in work for male youth.
Keywords: 330